Using computer–based tools and technology to improve jewellery design and manufacturing. (4th August 2014) - Lee, Han Boon; Ko, Michael S.H.; Gay, Robert K.L.; Leong, Kah Fai; Chua, Chee Kait
The focus on the use of computer–based tools for jewellery design and manufacturing takes on a new dimension with the advent of stereolithography technology. The research work undertaken studies the Singapore jewellery manufacturing practices in an attempt to upgrade the quality and quantity of production with the use of a comprehensive CAD/CAM system, stereolithography apparatus (SLA) and accompanying input and output devices. This paper outlines the present process of manufacturing jewellery, and shows how these traditional processes can be shortened through the use of computer–based tools and rapid prototyping technology.